Enhancing performance of multiwavelength Brillouin-Raman fiber laser by capturing residual pump power - Abass A.K.; Al-Mansoori M.H.; Jamaludin M.Z.; Abdullah F.; Al-Mashhadani T.F.; Ali M.H. (OSA - The Optical Society, 2023)
We demonstrate a simple design to enhance the performance of a multiwavelength Brillouin-Raman fiber laser by capturing the residual Raman pump power (RPP) from the laser cavity using a wavelength-selective coupler. The performance parameters of the laser system are investigated and compared with the conventional design under the same input design parameters. Both laser systems at a RPP of 375 mW can generate up to 33 Stokes lines with an equal channel spacing of 0.08 nm; however, the tunability of the laser without injection of residual RPP is 25% higher than the conventional laser structure. In addition, for a laser system without residual RPP injection, increasing the RPP improves the laser performance and generates up to 42 Stokes lines with a tunability of 24.5 nm, from 1570 to 1594.5 nm, at 475mW. In contrast, the laser system with a residual RPP has the worst performance as the pump power is increased, and generates only nine Stokes lines with a tuning range of 5 nm at the same RPP of 475 mW. © 2014 Optical Society of America.